Avraamidou, Maria - (:unkn) unknown (My University, 2026)
Maria Avraamidou is a PhD candidate at the Department of Communication and Internet Studies of the Cyprus University of Technology. She holds a BA in Law, from the Aristotle University of Thessaloniki, with merits (2003) and an MA in Multimedia, Journalism from Bournemouth University with merits (2006). She has worked as a Protection Officer at UNHCR and at Non-govermental organizations. She has also worked as a journalism and political correspondent with an emphasis on the Cyprus issue and inter-communal relations. Ms Avraamidou has conducted several workshops and seminars on the topics of her expertise including seminars to the Police Academy, trainings at the Asylum Service (Ministry of Interior) and the Reviewing Authority of Refugees (Republic of Cyprus) and for Non Govermental Organizations. In Feburuary 2010 she was employed by the Department of Communication and Internet Studies, TEPAK as a Research Associate in the field of “Ethnicities and Communication”.